Kraton G SEBS Block Copolymers - Roland, C.M. (Polymer Data Handbook, 2009)
Class Saturated thermoplastic elastomer Other manufacturers/suppliers/compounders: Vita Thermoplastic Polymers, TechnoCompound, Kraiburg TPE, PolyOne, GLS, Dexco Polymers, Teknor, Kuraray Major Applications Asphalt modifiers, adhesives, sealants, coatings, waterproofing applications, footwear, polymer modifiers, oil gels Properties of Special Interest: In general, thermoplastic elastomers (TPE) provide the mechanical properties of rubber in combination with the processing characteristics of plastics; recyclable; Kraton Gs are low-cost TPE with oxidative and thermal stability, good weathering, and UV and ozone resistance.